Impact of STATCOM Design Parameters on Voltage Distortion at the PCC - Grazia Todeschini (2018 IEEE Power & Energy Society General Meeting (PESGM), 2018)
The subject of this work is the investigation of the power quality impact resulting from connecting a STATCOM to a distribution system. The STATCOM is used to provide voltage regulation, however, this device has an impact on the power quality at the PCC. This impact will be quantified for different STATCOM configurations (including two-level and multilevel inverter), output filter design and modulation techniques. The main conclusion of the analysis is that the STATCOM does not significantly impact the low frequency harmonics, however, for some configurations the THD limits are exceeded. It will be shown that changing the modulation technique does not change significantly voltage distortion at the point of common coupling (PCC), while increasing the number of levels and modifying the output filter design have a more evident effect. Future work on this topic will include the study of more complex system with existing harmonic distortion prior to connecting the STATCOM, to evaluate interaction of this device with other sources of harmonics.